The death assemblage as a marker for habitat and an indicator of climate change: Georges Bank, surfclams and ocean quahogs. (15th June 2017) - Powell, Eric N.; Kuykendall, Kelsey M.; Moreno, Paula
Abstract: A comprehensive dataset for the Georges Bank region is used to directly compare the distribution of the death assemblage and the living community at large spatial scales and to assess the application of the death assemblage in tracking changes in species' distributional pattern as a consequence of climate change. Focus is placed on the biomass-dominant clam species of the northwest Atlantic continental shelf: the surfclam Spisula solidissima and the ocean quahog Arctica islandica, for which extensive datasets exist on the distributions of the living population and the death assemblage. For both surfclams and ocean quahogs, the distribution of dead shells, in the main, tracked the distribution of live animals relatively closely. Thus, for both species, the presence of dead shells was a positive indicator of present, recent, or past occupation by live animals. Shell dispersion within habitat was greater for surfclams than for ocean quahogs either due to spatial time averaging, animals not living in all habitable areas all of the time, or parautochthonous redistribution of shell. The regional distribution of dead shell differed from the distribution of live animals, for both species, in a systematic way indicative of range shifts due to climate change. In each case the differential distribution was consistent with warming of the northwest Atlantic. Present-day overlap of live surfclams with live ocean quahogs was consistent with the expectation that the surfclam's range is shifting into deeper water in response to the recent warming trend. The presence of locations devoid of dead shells where live surfclams nevertheless were collected measures the recentness of this event. The presence of dead ocean quahog shells at shallower depths than live ocean quahogs offers good evidence that a range shift has occurred in the past, but prior to the initiation of routine surveys in 1980. Possibly, this range shift tracks initial colonization at the end of the Little Ice Age. Highlights: Death and life assemblages for biomass-dominant surfclams and ocean quahogs are compared. Within-habitat shell dispersion relative to live animals was greater for surfclams. The regional distribution of dead shell indicated range shifts due to climate change. Live surfclams sans dead shells track recent colonization with Mid-Atlantic warming. Dead ocean quahogs track initial colonization at the end of the Little Ice Age.